THAT'S MY CREATOR'S REALM: UNDERSTANDING AFRICAN AMERICAN ASSISTED LIVING RESIDENTS' END-OF-LIFE PREFERENCES. (8th November 2019) - Kemp, Candace L; Bender, Alexis A; Quest, Tammie; Coyle, Mary H; Perkins, Molly M
Abstract: Assisted living, one of the fastest growing formal long-term care options for older adults in the U.S., increasingly is a site for end-of-life care.. Most residents are non-Hispanic and white, yet African Americans reside in these settings and relatively little is known about their end-of-life preferences. In this paper, we present an analysis of data collected as part of a larger five-year mixed-methods NIA-funded study (R01AG047048) examining end of life in assisted living. We analyze longitudinal qualitative data collected over two years in a large (>90 beds) care community catering to African American older adults. Drawing on 850 hours of participant observation, in-depth interviews with 25 residents, and record review data, we seek to: (a) understand residents' end-of-life preferences; and b) identify how and why preferences vary. Guided by principles of grounded theory, our analysis shows that most preferred a death where "you go to sleep and never wake up." Yet, residents varied in their preferences for the timing and location of death, nature of end-of-life care, and use of advanced directives. Age, health, health literacy, perceived quality of life, and not wanting to be a burden all influenced preferences. For most, religious beliefs were a key factor shaping these preferences. Perceiving that end of life, including how, when, where one dies, and the nature of suffering and care, ultimately is their "creator's realm, " led to the near universal conclusion: "I got no control over it." We discuss implications of these findings for improving end-of-life care for African American residents.